The use of Metaphors analysis in self-help books EFL learners: a corpus-based study (IR) - Nadia Hassan (2015)
Understanding figurative language in literature can be puzzling for students due to its ungrammatical form. Corpus-based metaphor analysis, however, provides the lens assisting the students to learn this figurative language. The objectives of this study are 1. to determine the variation of metaphors used in two types of self-help books about teenagers life, emotions, education, and finance; 2. to analyse the manner the authors manifest each concept through metaphors; 3. to discuss how the findings can contribute to the learning of metaphor in English as a Foreign Language (EFL). This study employed both quantitative and qualitative methods. The instruments used are a corpus that were extracted from two popular English self-help books which are The Chicken Soup for Teenage Soul and Rich Dad Poor Dad for Teens; Wmatrix concordance software supported with the USAS semantic tagger that can help in finding the frequency of occurrence of life, emotions, education and finance keywords related metaphors, to be later analyzed thoroughly by adopting Metaphor Identification Procedure (MIP) for conceptual metaphor determination purpose; and additionally, the Oxford and Merriam Webster English dictionaries were also used to facilitate the analyses and for fulfilling the reliability and validity aspects. The findings indicate that several authors across different areas of concern, share the same conceptual cognitive in using metaphorical expressions to bridge their ideas to their readers. The used abstract concepts of the metaphorical expressions in the self-help books were embodied into various concrete concepts like LIFE IS JOURNEY, EMOTIONS ARE LIQUID SUBSTANCES, FORCES, and STATES, EDUCATION IS BUILDING, FINANCE IS JOURNEY, WEALTH, BUSINESS and DEBT ARE BUILDINGS. Building this specialised self-corpus proved that the intention to see high samples of metaphors is achievable. It is found that doing metaphor analysis through corpus-based methodology can ease-up and save much time more rather than manually analysis. Additionally, knowing their conceptual embodiment of ideas may help students understanding or even translating English language literature texts with ease. Since the target of this study is to see the implication of the analyzed conceptual metaphors that may contribute to the learning of English as a Foreign Language (EFL).